The Impact of COVID-19 on Immigration Detention - Marouf, Fatma E. (Frontiers in Human Dynamics, 2021)
COVID-19 has spread quickly through immigration detention facilities in the United States. As of December 2, 2020, there have been over 7,500 confirmed COVID-19 cases among detained noncitizens. This Article examines why COVID-19 spread rapidly in immigration detention facilities, how it has transformed detention and deportation proceedings, and what can be done to improve the situation for detained noncitizens. Part I identifies key factors that contributed to the rapid spread of COVID-19 in immigration detention. While these factors are not an exhaustive list, they highlight important weaknesses in the immigration detention system. Part II then examines how the pandemic changed the size of the population in detention, the length of detention, and the nature of removal proceedings. In Part III, the Article offers recommendations for mitigating the impact of COVID-19 on detained noncitizens. These recommendations include using more alternatives to detention, curtailing transfers between detention facilities, establishing a better tracking system for medically vulnerable detainees, prioritizing bond hearings and habeas petitions, and including immigration detainees among the groups to be offered COVID-19 vaccine in the initial phase of the vaccination program. The lessons learned from the spread of COVID-19 in immigration detention will hopefully lead to a better response to any future pandemics. In discussing these issues, the Article draws on national data from January 2019 through November 2020 published by Immigration and Customs Enforcement (ICE) and Customs and Border Protection (CBP), two agencies within DHS. The main datasets used are detention statistics published by ICE for FY 2019 (Oct. 2018-Sep. 2019), FY 2020 (Oct. 2019-Sep. 2020), and the first two months of FY 2021 (Oct. 2020-Nov. 2020). These datasets include detention statistics about individuals arrested by ICE in the interior of the country, as well as by CBP at or near the border. Additionally, the Article draws on separate data published by CBP regarding the total number of apprehensions at the border based on its immigration authority under Title 8 of the United States Code, as well as the number of expulsions at the border based on its public health authority under Title 42 of the United States Code.